2006
DOI: 10.1124/mol.106.029595
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants for High-Affinity Zolpidem Binding to GABA-A receptors

Abstract: The imidazopyridine zolpidem (Ambien)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 38 publications
(47 reference statements)
2
42
1
Order By: Relevance
“…The lack of correlation with residue volume suggests that the effect of this mutation may relate to conformational changes associated with receptor activation, rather than binding, which may not be reflected by our model. In a recent study, Sancar et al (2007) reported automated docking of FNZ and zolpidem, which resulted in a FNZ position that differs significantly from our results. In this model, the N1-methyl substituent is directed toward the membrane and is buried in the binding site, the carboxyl group is in close proximity to ␥ 2 Arg144 and ␣ 1 Thr206, and a fluorine atom is located next to ␣ 1 Tyr209, with ␥ 2 Thr193 and ␥ 2 Arg194 located close to C5-phenyl moiety.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The lack of correlation with residue volume suggests that the effect of this mutation may relate to conformational changes associated with receptor activation, rather than binding, which may not be reflected by our model. In a recent study, Sancar et al (2007) reported automated docking of FNZ and zolpidem, which resulted in a FNZ position that differs significantly from our results. In this model, the N1-methyl substituent is directed toward the membrane and is buried in the binding site, the carboxyl group is in close proximity to ␥ 2 Arg144 and ␣ 1 Thr206, and a fluorine atom is located next to ␣ 1 Tyr209, with ␥ 2 Thr193 and ␥ 2 Arg194 located close to C5-phenyl moiety.…”
Section: Discussioncontrasting
confidence: 57%
“…This may indicate the existence of an additional favorable orientation in which the BZ directly contacts this residue, as proposed by Sancar et al (2007); however, the introduction of nonaromatic ␥ 2 F77L, Fig. 9.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, these results strongly suggest that amino acid differences in the N terminus of mouse and human 5-HT 3A Rs exert their differential actions by affecting gating, not binding. These loops also have been shown to play a significant role in modulation of GABA-induced currents by BZDs and other drugs binding at the BZD binding site on the GABA A R (Sancar et al, 2007;Padgett and Lummis, 2008). The role of loops C and F in the GABA-BZD modulatory mechanism differs from the proposed role of these loops in colchicine modulation in that loops C and F probably induce conformational changes that affect gating of the 5-HT 3A R. In the GABA A Rs, these loops are thought to not only affect gating but also to play a direct role in stabilization of the BZD binding site.…”
Section: Discussionmentioning
confidence: 99%
“…see Ref. 6), the molecular mechanism by which benzodiazepines mediate their effects is not yet clear.…”
mentioning
confidence: 99%